Real Exchange Rates And Fundamentals: Robustness Across Alternative Model Specifications, Algerian Case(1990-2019) - Chetbani, Saida; Mouhoubi, Aissa (جامعة الوادي - University of Eloued, 2021)
This paper explores the robustness of behavioural equilibrium exchange rate (BEER) and natural equilibrium exchange rate (NATRAX) models, focusing on the appropriate approach for the Algerian currency exchange model with Algerian dinar real bilateral rates as dependent variable. It consists, in the first step, to determinate the equilibrium real exchange rate using BEER approach developed by Macdonald (1995), and Natrex approach developed by Lim & Stein. Cointegration technics and VECM models are used in this step. In a second step, we should choose the appropriate approach by the comparison between the two approaches. Obtained results show that the Natrex approach is advantageous in terms of degree of misalignment for the Algerian currency case. Therefore, we can conclude that it can be closer to the Algerian economic specification.
Keywords: Equilibrium real exchange rate ; BEER ; NATREX ; Algerian Currency ; Misalignment